Studi korelasional: Meninjau kemampuan berpikir kritis siswa sekolah dasar berdasarkan resiliensi matematis - Fatimah, Ade Evi; Hasanah, Nurul; Wahyuni, Fitry (Journal of Didactic Mathematics, 2024)
This study employs a quantitative correlational design using a survey method to collect data on students' critical thinking skills and mathematical resilience. The purpose of the research is to analyze and describe the relationship between mathematical resilience and the critical thinking abilities of fourth-grade students at a public elementary school in Gebang District, Langkat Regency, North Sumatra Province, involving a sample of 24 students. The study was conducted during the second semester of the 2023/2024 academic year. The research instruments used include a critical thinking skills test and a mathematical resilience questionnaire. Data analysis techniques employed in this study consist of descriptive and inferential statistics to examine the relationship between mathematical resilience and students' critical thinking abilities. The hypothesis tests utilized include correlation analysis, regression analysis, and regression coefficients. The findings indicate that mathematical resilience contributes to students' critical thinking skills, showing a positive relationship of moderate strength. Specifically, the regression analysis reveals that mathematical resilience accounts for 22.5% of the variance in the critical thinking abilities of the fourth-grade students.